A água na cidade romana: perspetivas de investigação: o caso de Bracara Avgvsta - Morais, Rui (2018)
The use of the water in a Roman city is an extremely complex topic of discussion, not only because there are different approaches to the subject, but also because there are very few available data. In an attempt to respond to this issue we have chosen to divide the topic into two parts: firstly we focus our attention on the different research perspectives concerning the theme of water, and secondly we use the Roman city of Bracara Augusta as a case study.